Pengaruh Kepuasan Kerja Terhadap Turnover Intention Dengan Komitmen Organisasi Sebagai Variabel Intervening Pada Pt. Autobagus Rent Car Bali. - Putra, I Gst Ag Gd Emdy Mahardika; Wibawa, I Made Artha (E-Jurnal Manajemen; Vol 4 No 4 (2015), 2015)
The purpose of this study was to determine the effect between job satisfaction and turnover intention are mediated by organizational commitment at PT. Autobagus Rent Car Bali. The instrument used in this study was a questionnaire consisting of a number of statements regarding job satisfaction, turnover intention, and organizational commitment. This study uses saturated sample, where the entire study population will be selected into the sample as many as 98 people. Data analysis techniques used in this research is path analysis. The results showed that job satisfaction has a significant effect on turnover intentions directly and there is significant effect between job satisfaction on turnover intentions are mediated through organizational commitment. Keywords : job satisfaction, turnover intention, organizational commitment
Keywords: job satisfaction; turnover intention; organizational commitment